Changes in the Frequency of Cesarean Delivery in Nulliparous Women in Labor in a Canadian Population, 1992–2018. Issue 2 (February 2021) - Wood, Stephen; Tang, Selphee
Abstract : OBJECTIVE: To examine the relative contribution of changes in patient demographics and physician management to changes in the cesarean delivery rate in labor among nulliparous women. METHODS: We conducted a retrospective cohort study of 485, 451 births to nulliparous women who experienced labor at or beyond 35 weeks of gestation in Alberta, Canada, from 1992 to 2018. The data were from a province-wide perinatal database. The primary outcome was cesarean delivery. Multivariate logistic regression and calculation of population attributable risk for identified risk factors were performed. RESULTS: The cesarean delivery rate increased from 12.5% in 1992 to 24% in 2018. The prevalence of maternal risk factors for cesarean delivery such as obesity, maternal age 35 years or older at delivery, and comorbidities increased over the study period. However, this did not account for the increase in cesarean delivery, because the frequency of cesarean delivery increased irrespective of risk status. Additionally, the population-attributable risk for each risk factor was stable across the study period. For example, for maternal age 35 years or older at delivery, the number of cesarean deliveries attributable to this factor (the population-attributable risk) was 0.9 per 100 deliveries in 1992–1998 and 1 per 100 in 2014–2018. The proportion of cesarean deliveries in which nonreassuring fetal status was the indication increased from 30.1% in 1992 to 51.1% in 2018. The absolute rate of cesarean delivery in the second stage of labor increased from 3.1% in 1992 to 5.9% in 2018. This was due to a significant increase, among those who entered the second stage, in cesarean delivery without a trial of forceps, from 2.5% in 1992 to 7.0% in 2018. CONCLUSION: The observed doubling of the rate of cesarean delivery in labor in first-time mothers was not driven by patient risk factors. Increases in the rate of cesarean delivery for nonreassuring fetal status and decreased operative vaginal deliveries were important factors. Abstract : The increasing frequency of cesarean delivery in nulliparous women who experienced labor was not attributable to an increasing frequency of predisposing factors.